(untitled) (Revista Contexto & Educação, 2024)
The phenomenon of aging is a worldwide trend. This process is present in all life cycles, and awareness measures about individual and collective aging must be valued and developed in the educational context. This article proposed to carry out a bibliographic review on the content of aging in elementary education, through qualitative and quantitative research, in the selected databases, by the descriptors education, gerontology, elderly and elementary education, and their combinations. The inclusion criteria were complete publications, freely accessible between 2011-2021, in Portuguese, English, and Spanish. Of the productions found, 63 of them had low relevance and 2 had high relevance that reflected experiences in the Federal District and in the State of São Paulo, highlighting the importance of introducing themes about aging in schools in a structured way and aligned with the pedagogical curriculum, an experience indicated in educational policy of the State of São Paulo. This approach aligns with citizen development and participatory movements, which provide opportunities for actions and intersectoral articulation, projecting healthy aging measures to the community. This study shows itself to be relevant and highlights that intergenerational measures must be disseminated in the school context to eliminate prejudice and promote positive attitudes about aging.